Optical Emission Spectroscopy Study of the Electron Temperature and Electron Density Dependence on the Pressure Chamber for the Carbon Deposition Produced by Argon Plasma Sputtering. Issue 1 (May 2020) - Pambudi, D R S; Hanif, M A; Santjojo, D J D H; Padaga, M C; Masruroh,
Abstract: An investigation of the Optical Emission Spectroscopy (OES) to study the effect of the pressure chamber to the chemical species, electron temperature ( Te ) and electron density ( Ne ) was performed on RF 2 MHz plasma sputtering for carbon deposition. A carbon target and argon (Ar) gas were used to deposit carbon films. The carbon deposition was carried out at pressure chamber of 10, 15 and 20 Pa, and the RF voltage, flow rate and substrate temperature were kept at 120 volts, 60 ml/min, and 200°C, respectively. The emission spectrum of Ar plasma was monitored by OES in order to analyze the chemical species present in the plasma during the deposition process. The atomic spectroscopy data center (NIST) database was used to determine the species in the plasma and to calculate the Te and Ne . The OES emission shows the peak intensity which indicates the Ar I (Ar*) and Ar II (Ar + ion). The electron temperature was calculated using the Boltzmann Plot while the electron density was calculated using Stark Broadening. The results show that both Te and Ne decreased on the increasing of the pressure chamber. The emission line measurements with Boltzmann Plot resulted in the electron temperature dependence of pressure is approximately 0.487±0.005, 0.481±0.006, and 0.474±0.011 eV, respectively. Moreover, the calculation of electron density resulted in approximately (5.495 ± 0.407) × 10 18, (4.825 ± 0.384) × 10 18, and (4.515 ± 1.037) × 10 18 cm −3 .